Penyediaan Rumah Panggung Aman Banjir Bagi Mama Elisabeth Seuk Bete, Warga Jemaat GMIT Ebenhaezer Motaulun Kecamatan Malaka Barat Kabupaten Malaka - Damaris Y. Koli; Joni Kanisius Olin; Selviana Domingga Hoar (Universitas 45 Surabaya, 2023)
The flash flood that hit Malacca district as a result of the tropical cyclone storm in several areas of NTT, had a very severe impact on one village, namely Motaulun, located in West Malacca District, Malacca Regency. Motaulun village was the first door to receive water shipments because the embankment was broken not far from the village. Flash flooding is a flood that occurs suddenly and unexpectedly due to very heavy rain in the upstream or due to a broken dam. Flash floods with a height of more than 1 meter of water up to the height of an adult's neck for a full day, not only washed away the houses of Motaulun villagers, but also washed away all their belongings. One of the groups affected is the GMIT Ebenhaezer Motaulun Congregation which has 125 families with 270 people. The only house out of 62 houses located in Lookmi A hamlet is the house belonging to Elisabeth Seuk Bete (78 years old), which was washed away by the flood and all her belongings. The provision of flood-safe stilt houses has the aim of easing the burden of victims while at the same time realizing UKAW's care and concern through community service activities.